Iowa CBC reporting form, Iowa City, December 21, 1985 - Staudt, Thomas J.et al (1985)
Checklist dated December 21, 1985 compiled by Tom Staudt. A list of birds sighted by Staudt and thirty-six others around Iowa City. A total of 63 species and 7,546 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed